Evaluación del programa de apoyo del Ministerio de Inclusión Económica y Social a la Fundación María Jacinta Polo de Chone. - Molina Rengifo, Jessica Fernanda (2016)
The research consisted in carrying out an analysis of the program supported and provided by the Ministry of Economic and Social Inclusion together with GAD Chone to the Maria Jacinta Polo Foundation. For the gathering of information the deductive, inductive, historical and explorative methods were used; in addition to the field and descriptive research methods, which allowed to fulfill the objectives. In the first phase an interview to the MIES director was applied meeting the program and the assistance which they provide to the public, the director of the foundation explain that the support received by the Ministry is useful for the integral development of the older adults. In the second phase a survey was applied to older adults of the institution, which allowed to meet the degree of satisfaction of this group. Finally the last phase evaluated the program that provided to the Maria Jacinta Polo Foundation and determined the shortcomings that exist in this institution and requirements. It was determined that in recent years there has been an increase of older adults in the foundation.